Pengaruh Kepuasan Kerja terhadap Peningkatan Kinerja Karyawan pada PT Bintang Mas Pusaka Lubuklinggau - Yunita, Herma; Yansyah, Fitri (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study addresses the following questions: 1) what is the level of job satisfaction and employee performance at PT. Bintang Mas Pusaka? 2) How does job satisfaction affect employee performance at PT. Bintang Mas Pusaka? The research aims to: 1) Identify and describe job satisfaction and employee performance at PT. Bintang Mas Pusaka, and 2) Analyze the impact of job satisfaction on employee performance at the company. This is an associative study involving a population of 26 employees, with the entire population sampled using a saturated sampling method. Data for the research were collected through questionnaires, interviews, and observations, encompassing both primary and secondary sources. The research results indicate that job satisfaction has a significant positive impact on employee performance at PT. Bintang Mas Pusaka Lubuklinggau. This is evidenced by a t-test value of 11.894, which is substantially higher than the t-table value of 1.706, with a significance level of 0.000, which is less than α 0.05. This suggests that job satisfaction consistently and significantly influences the improvement of employee performance. Furthermore, the analysis reveals that the R Square value is 0.849 or 84.9%, indicating that nearly 85% of the variation in employee performance at the company can be explained by job satisfaction. Meanwhile, the remaining 15.1% of performance variation is influenced by factors not examined in this study. In other words, job satisfaction is a primary predictor contributing to employee performance, although other variables also play an important role.